From Yarn to Tomorrow: Unearthing Sustainable Textile Practices in India’s Past, Present, and Future - Agrawal, Supriti; Rajendra, Kushagra; Binzani, Vaidehi; Ghoshal, Ria (Nepalese Journal of Management Science and Research, 2024)
Indian textile industry is currently experiencing a shift towards sustainability in response to growing concerns about the environment and social issues. Textile industry is projected to reach a value of US $387.3 billion by 2028 and shows immense potential for adoption of eco-friendly and ethical practices. This research focuses on examining the historical development, current state, and future aspects of the industry. In the past, the industry has been associated with environmental degradation and exploitative labour practices. However, there is now a global movement towards reducing ecological impact and promoting fair working conditions. The objective of this study is to analyse ancient sustainable traditions in India to gain insights into the challenges faced by the apparel industry today. Further, it also explores past and current innovative practices and emphasizes the revival of traditional, eco-friendly techniques. This paper uses descriptive research. It employs a secondary data methodology, and an extensive review was conducted through scholarly literature, reports, and articles.